Bem Viver e protagonismo comunitário: importância da reafirmação identitária para relações responsáveis nas comunidades do Vale do Jari, Amapá - Macedo, Inaray Alexandra (Universidade Federal de São Carlos, 2025)
Buen Vivir is expressed as a life philosophy grounded in solidarity, reciprocity, and harmony with nature, assuming meanings that adapt to specific social and environmental contexts. This study examines the genuine expressions of Buen Vivir present in the traditional communities of São Francisco do Iratapuru, Santo Antônio da Cachoeira, and São José, located in the Vale do Jari (Amapá, Brazil). It seeks to understand how the meanings and values that constitute their ways of life contribute to identity-based self-affirmation, the promotion of socio-environmental conservation, and the construction of more responsible relationships between communities and external actors. The study also aims to explore how Buen Vivir supports the continuity of traditions and strengthens local ways of living, even in the face of external threats and dominant relations that jeopardize community integrity. The research adopts a qualitative approach, using semi-structured interviews, dialogue circles, and field observations conducted during two scientific expeditions to the Vale do Jari as part of the Amazônia+10 project. Data were analyzed using Bardin’s Content Analysis (2007), resulting in three main categories: Community Buen Vivir; Threats to Buen Vivir; and Community Protagonism. Each category contains subcategories that elucidate the identified dimensions, described on the basis of interview responses and complemented by field observations and collective discussions held during the dialogue circles. The results reveal strong interconnections among the categories, highlighting a form of Buen Vivir sustained by everyday practices, family and community relations, and a profound attachment to the territory. This occurs despite significant challenges stemming from limited infrastructure and external pressures that affect, to varying degrees, their ways of life. Even so, the communities demonstrate forms of organization that already reflect local agency, which can be further strengthened through the valorization of their histories and territorial markers—elements that shape their identity, culture, originality, and sense of belonging. These factors reinforce the communities’ claims to their territories and ways of living, shaping a deeply rooted sociocultural identity. Consequently, those who do not belong to these territories increasingly recognize themselves as visitors, acknowledging the community’s right to define rules that safeguard their ways of life and promote responsible interactions. In conclusion, this study represents an initial form of knowledge returned to the communities, emphasizing that their ways of life matter and that they are protagonists of their own histories. It aims to strengthen community self-affirmation while encouraging external actors to recognize and respect these ways of life, fostering more responsible relationships and contributing to the preservation of the sociocultural identity of the Vale do Jari.
Buen Vivir and community leadership: the importance of reaffirming identity for responsible relationships in the communities of the Jari Valley, Amapá
Keywords: Identidade sociocultural; Pertencimento; Sociobiodiversidade Amazônica; Autovalorização; OUTROS::CIENCIAS; 11. Cidades e Comunidades Sustentáveis; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável; 3. Saúde e Bem-Estar